In Defense of Knowing, In Defense of Doubting: Cicero Engages Totalizing Skepticism, Sensate Materialism, and Pragmatist Realism in "Academica" - Prus, Robert (Qualitative Sociology Review, 2006)
Whereas contemporary scholars in the social sciences and humanities often envision themselves as exceptionally, if not uniquely, attentive to the problematics of human knowing and acting, the competing philosophies of totalizing skepticism, sensate materialism, divine worldviews, and pragmatist realism have a much more enduring presence in Western social thought.Plato (c420-348BCE) introduces a broad array of philosophic standpoints (theological, idealist, skepticist, materialist, and pragmatist) in his texts and Aristotle (c384-322BCE) addresses human knowing and acting in more distinctively secular, pluralist terms. Still, more scholarly considerations of human knowing and acting would be comparatively neglected by Cicero’s time and even more so after his era.Although much overlooked by those in the human sciences, Cicero’s Academica re-engages a number of highly consequential issues pertaining to the matter of human knowing and acting. Likewise, whereas Christian theologians often were hostile to heathen (relativist, materialist, pragmatist) philosophic viewpoints, important residues of these approaches would remain part of the Western intellectual tradition though Augustine’s (c354- 430 BCE) works.Academica is centered on the historically sustained skepticist emphases of Plato’s Academy (c350-50CE) but Cicero’s text also attends to some competing viewpoints that developed along the way. In addition to (1) acknowledging some of the intellectual shifts in Plato’s Academy over three centuries, this statement also (2) provides a pragmatist critique of the totalizing skepticism of the Academicians, and (3) illustrates the ways in which Cicero, as a representative and defender of Academician skepticism, deals with critiques pertaining to the problem of human knowing and acting.Thus, whereas Cicero is best known as a rhetorician and his text is presented as an instance of rhetorical interchange, Cicero’s Academica also may be seen as “a defense of knowing” and “a defense of doubting,” two of the most central features of scholarship.